Executive summary: diagnosis and management of prosthetic joint infection: clinical practice guidelines by the Infectious Diseases Society of America - Osmon, Douglas R; Berbari, Elie F; Berendt, Anthony R; Lew, Daniel; Zimmerli, Werner; Steckelberg, James M; Rao, Nalini; Hanssen, Arlen; Wilson, Walter R (Clinical infectious diseases, 2013)
These guidelines are intended for use by infectious disease specialists, orthopedists, and other healthcare professionals who care for patients with prosthetic joint infection (PJI). They include evidence-based and opinion-based recommendations for the diagnosis and management of patients with PJI treated with debridement and retention of the prosthesis, resection arthroplasty with or without subsequent staged reimplantation, 1-stage reimplantation, and amputation.